Analisis Penerapan Fitur Rekomendasi Pemilihan Jasa Kurir pada Platform E-Commerce Berdasarkan Undang-Undang Nomor 5 Tahun 1999 Tentang Persaingan Usaha - Emma Yovela Sipahutar; Elisatris Gultom; Helza Nova Lita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The implementation of a recommendation feature in the courier service selection system on e-commerce platforms is a technological innovation aimed at improving logistics efficiency while providing a more optimal user experience. Through this feature, consumers can find alternative delivery services based on certain indicators, such as cost, estimated time, and service quality. However, in practice, the implementation of recommendation features has the potential to raise legal issues when platforms prioritize internal couriers or certain partners without transparency and clear objective indicators. This situation can lead to discriminatory treatment, limit market access for other businesses, and reduce consumer freedom in choosing services. This study aims to analyze the implementation of recommendation features by e-commerce platforms from a competition law perspective, specifically based on Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The method used is normative juridical research with a descriptive-analytical approach, through the review of secondary data in the form of laws and regulations, literature, and the practice of implementing recommendation systems in the digital industry. The research results indicate that recommendation features that unilaterally prioritize internal couriers without objective basis and without information transparency have the potential to violate Article 19 letter d of Law Number 5 of 1999. This practice can hinder competition, close opportunities for other courier service providers, and create distortions in the digital logistics ecosystem. Therefore, this study recommends that recommendation features in e-commerce be designed in a neutral, transparent manner, and based on objective indicators, such as rates, estimated delivery times, and service performance. This will maintain healthy business competition and protect consumers' rights to obtain the best service options.